Barriers and strategies to improve influenza vaccination in Pakistan - Muhammad J. Farrukh; Long C. Ming; Syed T.R. Zaidi; Tahir M. Khan (Elsevier, 2017)
Influenza vaccination is strongly recommended by World Health Organisation on a yearly basis. The rate of immunization in Pakistan is suboptimal. High cost, traditional norms, customs and low levels of education in Pakistan are preventing people from getting vaccinated. It is timely to include influenza vaccination in the expanded programme on immunization (EPI), which is a disease prevention programme aiming to eradicate preventable diseases through subsidized or free immunization. The Ministry of National Health Services, Regulation and Coordination, Government of Pakistan should launch a national influenza vaccine policy in view of this current situation and oversee its implementation. Healthcare professionals should promote influenza vaccination and focus on high risk groups such as the elderly, pregnant women and children. Convincing and educating family members regarding immunization of pregnant women and follow-up with parents regarding a second influenza shot for their children will further improve vaccination rates in Pakistan. Keywords: Vaccine, Refusal, Flu shot, Immunization, Traditional norms, Availability